Detection of cerebral perfusion abnormalities in acute stroke using phase inversion harmonic imaging (PIHI): preliminary results. Issue 6 (14th May 2004) - Eyding, J; Krogias, C; Wilkening, W; Postert, T
Abstract : Phase inversion harmonic imaging (PIHI) with newer contrast agents can display parameters of cerebral perfusion either using the established ipsilateral approach, or the novel bilateral approach in which both hemispheres are assessed in one examination. The aim of this study was to evaluate the potential of PIHI in detecting pathological perfusion in acute stroke, using the bilateral approach. Patients with a hemispheric syndrome presenting within 12 hours after symptom onset were examined with PIHI (SonoVue®; bolus kinetics, fitted model function) using the bilateral approach if possible. Semi-quantitative perfusion related parameters (time to peak intensity (TPI) and peak width (PW)) were evaluated, and results correlated to follow up cerebral computed tomography (CCT) scans. In these four preliminary cases (one ipsilateral, three bilateral), PIHI was able to identify the ischaemic region because the function could not be fitted to the data. In one case, there was a difference between a core region where no perfusion was seen, and a surrounding region where hypoperfusion was detected (prolonged TPI and reduced PW). PIHI was able to predict the localisation and size of the eventual infarction even if no early CCT signs were seen. Furthermore, in one case, a surrounding hypoperfused region was identified, where tissue survived after recanalisation of the initially occluded middle cerebral artery. Using the bilateral approach, two advantages in comparison with the ipsilateral approach were obvious: cortical structures could be evaluated, and only one examination was needed to compare unaffected (ipsilateral) with affected (contralateral) tissue. These results should be confirmed by more cases, and should also be correlated to acute perfusion/diffusion weighted MRI data.